Stepwise Weakening of Aeolian Activities During the Holocene in the Gannan Region, Eastern Tibetan Plateau - Yang, Shengli; Liu, Xiaojing; Cheng, Ting; Luo, Yuanlong; Li, Qiong; Liu, Li; Chen, Zixuan (Frontiers in Earth Science, 2021)
Aeolian sediments hold key information on aeolian history and past environmental changes. Aeolian desertification and extensive land degradation have seriously affected the eco-environment in the Gannan region on the eastern Tibetan Plateau. Understanding the history of aeolian activities can deepen our understanding of the impacts of climatic changes on aeolian activities in the future. This study uses a detailed chronology and multiple proxy analyses of a typical aeolian section in Maqu to reconstruct aeolian activities in the region during the Holocene. Our results showed that aeolian activities have occurred in the eastern Tibetan Plateau since the early Holocene. Magnetic susceptibility, grain size records, and paleosols formation indicated a trend of stepwise weakening in aeolian activities from the early Holocene to the present. The weakening of aeolian activities was divided into three stages: ~10.0–8.0 ka BP, ~8.0–4.0 ka BP, and ~4.0 ka BP to the present. Paleosols were primarily formed after ~8.0 ka BP, and episodically interrupted aeolian activities processes in the Gannan region. Aeolian activity may increase in the Gannan region as the climate gradually warms. Climatic changes and local hydrological conditions have jointly affected the history of aeolian activities in this region.